Analysis of interaction between the Arthrobacter sarcosine oxidase and the coenzyme flavin adenine dinucleotide by site-directed mutagenesis. - Nishiya, Y (1996)
Sarcosine oxidase from Arthrobacter sp. TE1826 (SoxA) tightly binds with the coenzyme flavin adenine dinucleotide (FAD). The amino-terminal region of this enzyme was recognized as a part of the FAD-binding domain by homology search analysis. Comparison with other structurally well-known flavoproteins suggested that the aspartate residue at position 35 (D-35) and the motif sequence (six residues at positions 12 to 17) were important for the interaction with FAD. Site-directed mutagenesis of each position was performed, and mutant SoxAs were purified and characterized. When D-35 was substituted with glutamate, asparagine, and alanine, it was indicated that the carboxyl group of the side chain interacted with FAD. Changes in the enzyme-bound FAD were also observed from the altered spectral profiles. Thirteen mutant SoxAs were obtained by replacing amino acids in the motif sequence. Most of them showed inhibited or remarkably decreased sarcosine oxidase activity, and their spectral profiles were altered. However, some of them were reactivated by chloride ion. Their spectral profiles also became close to that of wild type in the presence of chloride ion. These results strongly suggest that the inhibition of interaction of enzyme with FAD was caused by the substitution in the motif and that it could be recovered under different conditions.